População em situação de rua e questão social: uma revisão sistemática da literatura nos anais do Congresso Brasileiro de Assistentes Sociais (2016 a 2022) - Batista, Franciele Soares (Brasil, 2025)
The general objective of this Course Completion Work was to analyze the academic production of Brazilian Social Service, which has as its central focus the theme of the Homeless Population (PSR) and its relationship with the social issue, based on the Systematic Literature Review (RSL) in Annals of the Brazilian Congress of Social Workers (2016, 2019 and 2022 Editions). As specific: problematize, at a theoretical level, the theme of PSR and its links with the category of social issue; Characterize the works present in the CBAS Annals; Reflect on the academic production of the Annals that deal with PSR, highlighting the importance of Social Work in this context. As a methodology, it is a bibliographical research based on the RLS procedure. The results indicate a total of 74 works in the three annals researched that have PSR as a research topic. A highlight in the 2022 Annals concerns the production that privileged the discussion of Covid-19 and its impacts on the PSR. At the same time, this research highlights the importance that Social Service researchers and professionals have given to the topic of PSR from the perspective of social law.